...If you traveled on the underground railroad - Levine, Ellen; Johnson, Larry, 1949- (New York : Scholastic, 1993)
Explains what the Underground Railroad was, why slaves ran away, and how they were helped to escape.
K-3.
720
Accelerated Reader AR
Keywords: Underground Railroad -- Juvenile literature; Underground Railroad